2013
DOI: 10.1016/j.jpain.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Pain Education at the University of Washington School of Medicine

Abstract: Contemporary medical education is inadequate to prepare medical students to competently assess and design care plans for patients with acute and chronic pain. The time devoted to pain education in most medical school curricula is brief and not integrated into case-based clinical experiences, and it is frequently nonexistent during clinical clerkships. Medical student pain curricula have been proposed for over 30 years and are commonly agreed upon, though rarely implemented. As a consequence of poor undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 30 publications
1
77
0
2
Order By: Relevance
“…In response, new and portable curricula and competencies are being developed in medical, nursing, pharmacy and other schools for the allied health professions . Incorporating information technology into the delivery of curricula has strengthened CME .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, new and portable curricula and competencies are being developed in medical, nursing, pharmacy and other schools for the allied health professions . Incorporating information technology into the delivery of curricula has strengthened CME .…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating information technology into the delivery of curricula has strengthened CME . Innovative teaching approaches include mentoring by means of video technology and this “telementoring” has been described in the literature as a reasonable method for delivering focused CME . This article details a telementoring CME/CPD innovation that is a potential solution to developing chronic pain expertise among health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a multidisciplinary group of experts, including among others representatives from the European Federation of the International Association for the Study of Pain (IASP), launched a pan‐European initiative aiming at highlighting the importance of undergraduate pain education, as inadequate or nonexistent pain management training is still the norm in European medical schools [10]. The problem is equally evident in North America; although medical school pain curricula have been proposed for over 30 years, they are rarely implemented, with very little time devoted to pain education in the majority of American medical schools [8,11,12]. In specific, in a systematic review of 117 U.S. and Canadian medical schools, Mezei and Murinson reported considerable gaps between recommended pain curriculum and actual educational content in medical school education related to pain management [11].…”
Section: Introductionmentioning
confidence: 99%
“…3,5,19,29,33 A survey of 117 U.S. and Canadian medical schools 21 found that while most provided some pain content embedded in general courses, many topics recommended in the International Association for the Study of Pain (IASP) core curriculum 15 received little to no coverage. In general, Canadian schools provided more extensive pain education than did their U.S. counterparts.…”
Section: Introductionmentioning
confidence: 99%